Kecak sebagai Seni Pertunjukan Monumental dan Representasi Identitas Budaya Bali - I Nyoman Mariyana; Gek Diah Desi Sentana (CITRAKARA, 2025)
Kecak is a Balinese performing art that holds a monumental position in the Indonesian cultural landscape. Rooted in the sacred Sanghyang ritual, Kecak has undergone a transformation into a communal, aesthetic, and communicative performing art without losing its symbolic meaning. This article aims to examine Kecak as a monumental performing art as well as a representation of Balinese cultural identity. A qualitative approach is used through literature studies, performance observations, interviews, documentation and conceptual analysis of performing arts and cultural identity theory. The results of the study indicate that Kecak's monumentality lies in the dimension of the method used in this writing using qualitative descriptive research. Kecak has become the strongest representation (sign) of Balinese cultural identity and has given birth to various forms of art such as; Body Tjcak, "Kobagi", "Elektrik Kecak", "Perkusi Kecak", Cak Air, as well as symbolic power that represents the spiritual, social, and cosmological values ​​of Balinese society. Kecak not only functions as an aesthetic spectacle, but also as a medium for the articulation of Balinese cultural identity that continues to be negotiated amidst the dynamics of tourism and globalization. Thus, Kecak can be understood as a performing art that plays an important role in preserving, representing, and strengthening Balinese cultural identity both locally and globally.